URGENSI PEMBENTUKAN MAJELIS PROFESI PENERBANGAN DI TINJAU DARI PASAL 364 UNDANG-UNDANG NOMOR 1 TAHUN 2009 TENTANG PENERBANGAN - Dimitri Ilyasa; Amad Sudiro (Jurnal Hukum Adigama, 2022)
In the world of aviation, aircraft accidents often occur, especially in Indonesia, which are caused byfactors such as weather, technical conditions of aircraft, airport technical conditions, humannegligence, and various other causes. Due to human negligence, it is necessary to establish anAviation Professional Council which will improve the competence of aviation personnel and upholdprofessional ethics in the Indonesian aviation world. Therefore, it is necessary to establish an AviationProfessional Council in Indonesia in accordance with Article 364 of Law Number 1 of 2009concerning Aviation (hereinafter referred to as the Aviation Law) whose function is to provideadministrative sanctions to flight personnel who are negligent or do not perform their professionaccording to procedures that cause aircraft accidents and provide legal protection for AviationPersonnel who are considered to have violated the code of ethics and or mis-procedures in carryingout their profession so that they are not subject to criminal or civil sanctions if in further investigationthere is no indication of intent.